Indirect evidence of the composition of nucleation mode atmospheric particles in the high Arctic. Issue 2 (30th January 2016) - Giamarelou, Maria; Eleftheriadis, Konstantinos; Nyeki, Stephan; Tunved, Peter; Torseth, Kjetil; Biskos, George
Abstract: Previous long‐term observations have shown that nanoparticle formation events are common in the summer‐time high Arctic and linked to local photochemical activity. However, current knowledge is limited with respect to the chemical precursors of resulting nanoparticles and the compounds involved in their subsequent growth. Here we report case‐study measurements during new particle formation (NPF) events of the particle size distribution (diameter > 7 nm) and for the first time the volatility of monodisperse particles having diameter ≤40 nm, providing indirect information about their composition. Volatility measurements provide indirect evidence that a predominant fraction of the 12 nm particle population is ammoniated sulfates in the summertime high Arctic. Our observations further suggest that the majority of the sub‐40 nm particle population during NPF events does not exist in the form of sulfuric acid but rather as partly or fully neutralized ammoniated sulfates. Key Points: Volatility measurements of monodisperse nanoparticles in the high Arctic Compounds involved in particle growth during nucleation are indirectly identified Findings show that 12 nm particles mainly consist of ammoniated sulfates